Contestation of Interests in the Development of Civil Virtue in the Nagari Community - Aizil, Septri; Moeis, Isnarmi; Rafni, Al; Afdhal, Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the dynamics of interest contestation in developing civic virtue within Nagari communities, specifically focusing on Nagari Sungai Pua following the 2023 Nagari Head Election (PILWANA). Through qualitative descriptive research conducted over three months (October-December 2023), involving 25 key informants from various social elements, this study reveals how political contestation significantly influences the development of civic values in traditional communities. The findings demonstrate that interest contestation manifests in three primary dimensions: social fragmentation patterns, transformation of collective decision-making mechanisms, and reconfiguration of traditional value systems. The research identifies that post-election polarization has created complex alliance networks transcending traditional tribal boundaries, affecting both formal social structures and informal community dynamics. Furthermore, the study highlights how modernization pressures have led to the development of sophisticated filtering mechanisms in selecting and adapting new values while maintaining fundamental principles rooted in local traditions. This research contributes to understanding how traditional communities navigate the challenges of maintaining civic virtue amid contemporary political dynamics, offering insights for policy development in local governance strengthening and social cohesion enhancement. The study suggests that successful civic virtue development depends heavily on the community's ability to manage interest contestation through constructive dialogue and public deliberation, emphasizing the importance of developing inclusive strategies that bridge various stakeholder interests while preserving traditional values.